Right-Wing Terrorism in the 21st Century: The 'National Socialist Underground' and the History of Terror from the Far-Right in Germany - Koehler, Daniel (Routledge Studies in Fascism and the Far Right, 2016)
Cover -- Title -- Copyright -- Dedication -- Contents -- List of figures -- List of tables -- Foreword -- Acknowledgements -- List of abbreviations -- 1 Introduction -- 2 Methods and sources - the Database on Terrorism in Germany (DTG) -- 2.1 Review of existing research -- 3 The definition problem -- 3.1 Terrorism and right-wing terrorism as concepts -- 3.2 Hate crimes and terrorism -- 3.3 A typology of right-wing criminal activities -- 3.4 Conclusion -- 4 Right-wing violence and terrorism in post-Second World War Germany -- 4.1 The emergence of right-wing terrorism -- 4.2 Lone actors